Analysis of Easy Perception of Use of Information System Using Technology Acceptance Model Method - Basuki Heri Winarno; Edy Prayitno; Said Teguh Samudra (Journal of International Conference Proceedings (JICP), 2019)
Information systems are developed to improve the quality of business processes of an organization. In the use of information systems must pay attention to the ease of use by users. This study will analyze the perception of the ease of use of an information system for its users. The research was conducted using the Technology Acceptance Model method to test the user's acceptance of the information system used. Answers from users to questionnaire questions will be calculated and analyzed. As an object of research used a service clock information system that has been applied in a watch shop. The research conducted obtained results that the existing information system has provided a perception of ease of use in shop employees, with the results of the outer model values, discriminant validity (discriminant validity), construct reliability, R square, and valid T-statistic.